Biochemical status of serum iron in histopathological grades of oral submucous fibrosis - Toniya Raut; Shashi Keshwar; Jyotsna Rimal; Madhab Lamsal; Ashish Shrestha (Journal of Oral Biology and Craniofacial Research)
Background: Oral submucous fibrosis is a multifactorial, chronic disease of oral mucosa characterized by mucosal atrophy and fibrosis leading to functional morbidity; amongst many iron deficiency is considered as one of the risk factor. Also the iron level is considered to be depleted due to increased utilization during collagen synthesis. This study was conducted to evaluate the level of iron in patients with fibrosis and correlate with different histopathological grades. Methods: A total of 40 clinically diagnosed and histopathologically confirmed cases of submucous fibrosis were considered. Clinical data were recorded and status of iron was estimated through serum iron and total iron binding capacity by ferrozine method using a digital auto-analyzer. The level of iron was correlated with the histopathological grades and epithelial dysplasia. Result: The mean age of patients was 37.07 ± 14.63 years with the male to female ratio of 6.5:1. Areca nut consumption was associated with all the cases among which 87.5% of cases were exposed to commercial forms. 37.5% of cases were in early grade whereas 60% in moderately advanced histopathological grade. The level of mean serum iron and total iron binding capacity was higher in moderately advanced than in early grade. However no statistically significant difference was observed within the histopathological grades. Conclusion: Iron is influenced by many factors like dietary intake, food habits, metabolic reactions, chronic diseases, etc. Serum iron is reduced in patients with oral submucous fibrosis which should be supplemented to impede the carcinogenic potential and improve the treatment outcome.